2011
DOI: 10.1100/tsw.2011.59
|View full text |Cite
|
Sign up to set email alerts
|

Plasmablastic Lymphoma: A Systematic Review

Abstract: Plasmablastic lymphoma (PBL) is a very aggressive variant of diffuse large B-cell lymphoma initially described in the oral cavity of HIV-infected individuals. PBL represents a diagnostic challenge given its characteristic morphology and lack of CD20 expression, and also a therapeutic challenge, with early responses to therapy, but with high relapse rates and poor prognosis. In recent years, our understanding and clinical experience with PBL has increased in both HIV-positive and -negative settings. However, gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
170
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 138 publications
(172 citation statements)
references
References 55 publications
0
170
0
1
Order By: Relevance
“…(3) PBL has a high incidence in HIV-positive patients and is more common in men. (2) PBL also seems to be more common in patients who have weakened immune systems due to infection by EBV or human herpes virus 8. Castillo et al, (4) who described the greatest number of PBL cases (n = 228), reported that 69% of patients (mean age = 39 years) were HIV-positive, and that most HIV-negative patients (mean age = 58 years) were EBV-positive.…”
Section: A S E R E P O R Tmentioning
confidence: 99%
See 4 more Smart Citations
“…(3) PBL has a high incidence in HIV-positive patients and is more common in men. (2) PBL also seems to be more common in patients who have weakened immune systems due to infection by EBV or human herpes virus 8. Castillo et al, (4) who described the greatest number of PBL cases (n = 228), reported that 69% of patients (mean age = 39 years) were HIV-positive, and that most HIV-negative patients (mean age = 58 years) were EBV-positive.…”
Section: A S E R E P O R Tmentioning
confidence: 99%
“…Extranodal lymphoid organs, the central nervous system, peripheral lymph nodes, paranasal sinuses, mediastinum, lung, liver, and bone marrow may also be involved. (2) There have been recent reports of PBL in HIVnegative patients in whom the lesions mostly occurred in the extranodal tissues, including the skin, soft tissue, maxillary sinus, and gastrointestinal tract. There has been only one previous report of a simple breast PBL lesion.…”
Section: A S E R E P O R Tmentioning
confidence: 99%
See 3 more Smart Citations